Vitiligo/Lichen sclerosus of the genital skin. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Vitiligo and lichen sclerosus can be easily distinguished from a clinical point of view. Some problem may arise when these disorders are exclusively localized on the genital area, where the white color of lichen sclerosus can be confused with that one of vitiligo.